The Contribution of Entrepreneurial Competence of Madrasah Principals to Improve Graduate Quality: - - AS'ARI, As’ari; Syarifuddin2, Encep; Apud, Apud (International Journal of Education, Teaching, and Social Sciences, 2024)
Madrasas are required to transform and improve graduates' education quality, and they do not become a second alternative. Madrasas are less responsive to any potential development of madrasas' environment concerning madrasa's real-life situations and the concentration of madrasas' efforts. The principal's entrepreneurial competence is needed to solve this problem. The research aims to prove the contribution of school principals' entrepreneurial competence to improving the quality of madrasah graduates. This research applied the quantitative and inferential methods in which infinite numeral-based data was analyzed from the response to questions of both variables using simple linear regression. The population of the research was teachers at the Banten Province State Madrasah Aliyah. Samples were obtained by stratified random sampling, which amounted to 200 people. The research findings (regression-based analyses) showed that the criteria for p < 0.005 were fulfilled, so school entrepreneurial competence was significantly proven to improve graduates' quality at the Banten Province State Madrasah Aliyah. Based on the results of this study, the entrepreneurship of madrasah principals not only focuses on financial aspects but also on efforts to create added value for all stakeholders, significantly improving the quality of graduates